2007
DOI: 10.1001/archotol.133.4.350
|View full text |Cite
|
Sign up to set email alerts
|

Construct Validity of the Endoscopic Sinus Surgery Simulator

Abstract: Objectives: To establish discriminant validity of the endoscopic sinus surgery simulator (ES3) (Lockheed Martin, Akron, Ohio) between various health care provider experience levels and to define benchmarking criteria for skills assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(18 citation statements)
references
References 18 publications
1
16
1
Order By: Relevance
“…The ES3 was clearly able to distinguish between the three levels in initial trials, with the expert performing at the highest level, followed by residents, then medical students. This study also showed that all groups achieved a remarkably similar plateau score by the tenth trial on the simulator, demonstrating the ability of the ES3 to consistently achieve a standard performance goal in users (Fried et al 2007). The most recent validation study (“Virtual Reality to Operating Room”, or “VR to OR”), which provides the strongest clinical correlation, evaluates whether training on the ES3 translates to improved performance in actual surgery.…”
Section: Introductionmentioning
confidence: 56%
“…The ES3 was clearly able to distinguish between the three levels in initial trials, with the expert performing at the highest level, followed by residents, then medical students. This study also showed that all groups achieved a remarkably similar plateau score by the tenth trial on the simulator, demonstrating the ability of the ES3 to consistently achieve a standard performance goal in users (Fried et al 2007). The most recent validation study (“Virtual Reality to Operating Room”, or “VR to OR”), which provides the strongest clinical correlation, evaluates whether training on the ES3 translates to improved performance in actual surgery.…”
Section: Introductionmentioning
confidence: 56%
“…If applicable, the results could be compared competitively to those of other test candidates [669], [682], [683]. Although the benefit for effective surgical dissection was sometimes estimated to be low [84], [684], new comparative studies already reveal a positive approach, at least partially [10].…”
Section: Training Issuesmentioning
confidence: 99%
“…1 The Lockheed Martin Corporation (Akron, Ohio, US) has recently developed a nasal and paranasal sinus endoscopic surgery virtual simulator -the ES3 -based on flight simulator concepts developed previously at this company for the North-American military forces. 1,10,[24][25][26] This simulator applied virtual reality and direct user interaction mechanisms, such as force feedback. Its use, however, remains restricted, even in the US, due to the high cost of equipment, which includes a powerful computer (Silicon Graphics Inc., Mountain View, Calif), force feedback controls (Phantom Omni), and a platform consisting of a replica of an endoscope, surgical tools, and a model plastic head (Fig.…”
Section: Rhinologymentioning
confidence: 99%
“…Most of them show positive results of training of medical students and residents. [24][25][26] This model, however, has certain disadvantages, such as high cost, the use of virtual images that are often confusing and have poor resolution, sensitive changes upon touching certain structures, and the impossibility of handing real tools and endoscopes used in traditional surgery. 26,27 Prodelphus (www.prodelphus.com; Recife, Pernambuco, Brazil) and Brazilian physicians have developed a nasosinusal endoscopy dissection real model.…”
Section: Rhinologymentioning
confidence: 99%